LITERASI DIGITAL SAFETY PESERTA DIDIK SEKOLAH DASAR DI KECAMATAN CINEAM - Shinta Auliamaudy, - (2023)
This research is a survey research to reveal the digital safety literacy level of elementary school students. This research is based on the use of gadgets and social media that are familiar to students at the elementary school level, but it is feared that students lack knowledge of digital security in their use. So this study intends to reveal the level of digital safety literacy of students in elementary schools. The research was carried out by following the stages of survey research, and the data collection process used a questionnaire instrument. This research was conducted at five elementary schools in Cineam District, Tasikmalaya Regency. Questionnaire data calculations were processed using SPSS V16. The data that has been processed is then presented in a descriptive form based on the resulting data from the researcher to draw conclusions. The results showed that 76% of students in Cineam District expressed a positive response, namely they strongly agreed and agreed with digital track record literacy and students were also able to understand digital goals so they could receive information received on social media. 72% of students in the Cineam District expressed a positive response in understanding digital security when playing gadgets and social media so that they were able to implement digital security when playing gadgets and social media. From the results of the data obtained it was concluded that elementary school students in the Cineam District had a literacy level digital security and literacy digital track record is quite good. Keyword: Literacy, Digital Safety, Digital Record, Elementary Student